Mali : First and Second Reviews Under the Extended Credit Facility Arrangement, Request for Waiver of Performance Criteria, and Request for Modification of Performance Criteria. (IMF Staff Country Reports; Country Report ;, 2014)
This paper discusses Mali's First and Second Reviews Under the Extended Credit Facility Arrangement, Request for Waiver of Performance Criteria (PC), and Request for Modification of PC. Economic recovery is under way but remains fragile. The buildup of the large-scale donor support has been hampered by serious lapses in public financial management (PFM), which raised governance concerns. With remedial measures now in place to address the PFM weaknesses, the program remains on track. The authorities are requesting waivers for PC on: tax revenue and nonconcessional borrowing. The IMF staff recommends conclusion of the first and second program reviews.